Relation of infant feeding to adult serum cholesterol concentration and death from ischaemic heart disease. Issue 6830 (28th March 1992) - Fall, C. H.; Barker, D. J.; Osmond, C.; Winter, P. D.; Clark, P. M.; Hales, C. N.
Abstract : OBJECTIVE--To examine whether method of infant feeding is associated with adult serum lipid concentrations and mortality from ischaemic heart disease. DESIGN--Follow up study of men born during 1911-30. SETTING--Hertfordshire, England. SUBJECTS--5718 men, for 5471 of whom information on infant feeding had been recorded by health visitors and 1314 of whom had died. 485 of the men born during 1920-30 and still living in Hertfordshire who had blood lipid measurements. MAIN OUTCOME MEASURES--Death from ischaemic heart disease; serum cholesterol and apolipoprotein concentrations. RESULTS--474 men had died from ischaemic heart disease. Standardised mortality ratios were 97 (95% confidence interval 81 to 115) in men who had been breast fed and had not been weaned at 1 year, 79 (69 to 90) in breast fed men who had been weaned at 1 year, and 73 (59 to 89) in men who had been breast and bottle fed. Compared with men weaned before one year men not weaned had higher mean serum concentrations of total cholesterol (6.9 (not weaned) v 6.6 (weaned) mmol/l), low density lipoprotein cholesterol (5.0 v 4.6 mmol/l) and apolipoprotein B (1.14 v 1.08 g/l). Men who had been bottle fed also had a high standardised mortality ratio for ischaemic heart disease (95; 68 to 130) and high mean serum concentrations of total cholesterol (7.0 mmol/l), low density lipoprotein cholesterol (5.1 mmol/l), and apolipoprotein B (1.14 g/l). In all feeding groups serum apolipoprotein B concentrations were lower in men with higher birth weight and weight at 1 year. CONCLUSIONS--Age of weaning and method of infant feeding may influence adult serum low density lipoprotein cholesterol concentrations and mortality from ischaemic heart disease. Adult serum apolipoprotein B concentrations are related to growth in fetal life and infancy.